2018
DOI: 10.1007/s00384-018-3145-0
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic intersphincteric resection for low rectal cancer: a systematic review and meta-analysis

Abstract: Robotic and laparoscopic ISR showed comparable perioperative outcomes, functional outcomes, and 3-year oncologic outcomes; however, robotic ISR was associated with a lower conversion rate and less blood loss despite longer operation times compared to laparoscopic ISR. These findings suggest that robotic ISR maybe a safe and effective technique for treating low rectal cancer in selected patients. The potential oncologic and functional benefits of robotic ISR should be evaluated in larger randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 41 publications
6
70
4
Order By: Relevance
“…The LS group had longer proximal resection margin; however, no differences were observed regarding distal margin, TME status, and adequacy of lymph node retrieval, which was concordant with previous literatures [19][20][21]. Regarding the number of harvested lymph nodes, a lesser amount was noted in the RS group, of which was the same as that observed by Lee et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…The LS group had longer proximal resection margin; however, no differences were observed regarding distal margin, TME status, and adequacy of lymph node retrieval, which was concordant with previous literatures [19][20][21]. Regarding the number of harvested lymph nodes, a lesser amount was noted in the RS group, of which was the same as that observed by Lee et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…A reduction in the EBL was reported in a series of metaanalyses published on RRS in comparison to LRS and ORS. This reduction was observed in studies that evaluated RRS versus LRS [9,19,20,23] and those that assessed RRS versus ORS [9]. Shiomi et al [33] reported that in RRS, the EBL was 10.5 mL in obese patients and 10.0 mL in non-obese patients without a significant difference (P=0.83), whereas in LRS, the EBL was 34.0 mL in obese patients and 13.0 mL in non-obese patients with a significant difference (P= 0.02).…”
Section: Estimated Blood Lossmentioning
confidence: 84%
“…A longer operative duration was the most consistent shortterm outcome in the series of meta-analysis and RCTs published on RRS for rectal cancer [8,9,[18][19][20][21][22][23][24], (Table 1). Jayne et al reported [8] that the mean operative duration was 37.5 min longer with RRS than with LRS performed by a surgeon experienced with a median of 91 LRS and 50 RRS cases.…”
Section: Operative Duration and Learning Curvementioning
confidence: 96%
See 2 more Smart Citations